Transparent Nd-doped Ca1 − xYxF2 + x ceramics prepared by the ceramization of single crystals. (5th January 2017) - Jiang, Yiguang; Jiang, Benxue; Zhang, Pande; Chen, Shuilin; Gan, Qijun; Fan, Jintai; Mao, Xiaojian; Jiang, Nan; Su, Liangbi; Li, Jiang; Yu, Haohai; Zhang, Long
Abstract: Transparent Nd-doped Ca1 − x Yx F2 + x ceramics were obtained through the ceramization of single crystals, and the morphology, microstructural characteristics, optical properties, and laser performance of the ceramics were examined. The results indicated that the microstructure of the transparent Nd-doped Ca1 − x Yx F2 + x ceramics was similar to that of traditional hot-pressed CaF2 ceramics. In addition, the transparent Nd-doped Ca1 − x Yx F2 + x ceramics exhibited the same optical properties as the precursor single crystals. Furthermore, the ceramization of the precursor single crystals produced transparent Nd-doped Ca1 − x Yx F2 + x ceramics with mechanical properties (microhardness H = 3.430 GPa, fracture toughness K 1c = 0.61 MPa m 1/2 ) that were superior to that of the Nd-doped Ca1 − x Yx F2 + x single crystals. Continuous-wave laser operation with an output power of 35 mW was obtained through the application of a fiber-coupled laser diode with a central wavelength of approximately 808 nm. This suggests that the transparent Nd-doped Ca1 − x Yx F2 + x ceramics fabricated in this study are promising candidates for diode-pumped solid-state lasers and laser amplifiers. Graphical abstract: Highlights: Ceramization of single crystals technique was developed. Nd-doped Ca1 − x Yx F2 + x transparent ceramic was prepared by ceramization of single crystal. The sample exhibits high transmittance (T1053nm = 93.7%) and good mechanical properties ( H = 3.4 GPa, K 1c = 0.61 MPa m 1/2 ). The continuous wavelength laser operation was obtained with an output power of 35 mW by a fiber-coupled laser-diode.